Delta-like factor 1 negatively regulates angiogenesis as a target gene of miR-126-5p after indirect revascularization surgery in patients with moyamoya disease - Yang, Yang; Ling, Cong; Gao, Shuangqi; Li, Chao; Bhattarai, Robin; Wang, Hui; Chen, Chuan (Nepal Journal of Neuroscience, 2022)
Promoting endothelial cell (EC) proliferation and angiogenesis after indirect revascularization surgery is crucial for decreasing the stroke rate in moyamoya patients. However, the role of delta-like factor 1 (DLK1) in regulating EC proliferation in chronically ischaemic brains and the specific mechanisms remain unclear. Therefore, we compared the expression levels of DLK1 in the dura mater (DM) tissues of patients with moyamoya disease and patients with aneurysms, and dual luciferase reporter and RNA binding protein immunoprecipitation assays were conducted to determine whether DLK1 is a target gene of miR-126-5p. The effect of DLK1 on EC proliferation and the interaction between DLK1 and miR-126-5p were explored in vitro. Then, we established an animal model of two-vessel occlusion together with encephalo-myo-synangiosis (2VO+EMS). The temporalis muscles (TMs) of the animals were transfected with DLK1 lentiviral RNA (Lv-DLK1) and short hairpin RNA (sh-DLK1) to compare the DLK1 expression, angiogenesis (CD31 count), and numbers of vacuoles and impaired tight junctions in the ECs of TM-covered chronically ischaemic brains as well as the cognitive improvement in each group. DLK1 expression was lower in the DM tissues of moyamoya patients than in those of the aneurysm patients, and DLK1 was identified as a target gene of miR-126-5p. In vitro, DLK1 inhibited EC proliferation, migration and angiogenesis and exerted effects opposite those of miR-126-5p. In 2VO+EMS rats, compared to the control transfection, the TM transfection of Lv-DLK1 induced significantly higher DLK1 expression and worse angiogenesis in the TM-covered ischaemic brain as well as less extensive cognitive improvement, while the transfection of sh-DLK1 into the TM had the opposite effects. In summary, DLK1, a target gene of miR-126-5p, negatively regulates angiogenesis in chronically ischaemic brains and is expected to be a new target to improve the efficacy of indirect revascularization surgery and the prognosis of moyamoya patients.